A noncompeting pair of human neutralizing antibodies block COVID-19 virus binding to its receptor ACE2 - Wu, Yan; Wang, Feiran; Shen, Chenguang; Peng, Weiyu; Li, Delin; Zhao, Cheng; Li, Zhaohui; Li, Shihua; Bi, Yuhai; Yang, Yang; Gong, Yuhuan; Xiao, Haixia; et al. (Science (American Association for the Advancement of Science), 2020)
One of the responses of the immune system to invading viruses is the production of antibodies. Some of these are neutralizing, meaning that they prevent the virus from being infectious, and can thus be used to treat viral diseases. Wu et al. isolated four neutralizing antibodies from a convalescent coronavirus disease 2019 (COVID-19) patient. Two of the antibodies, B38 and H4, blocked the receptor binding domain (RBD) of the viral spike protein from binding to the cellular receptor, angiotensin-converting enzyme 2 (ACE2). The structure of the RBD bound to B38 shows that the B38-binding site overlaps with the binding site for ACE2. Although H4 also blocks RBD binding to ACE2, it binds at a different site, and thus the two antibodies can bind simultaneously. This pair of antibodies could potentially be used together in clinical applications. Science , this issue p. 1274 A pair of neutralizing antibodies against COVID-19 bind to different epitopes to compete with cellular receptor binding. Neutralizing antibodies could potentially be used as antivirals against the coronavirus disease 2019 (COVID-19) pandemic. Here, we report isolation of four human-origin monoclonal antibodies from a convalescent patient, all of which display neutralization abilities. The antibodies B38 and H4 block binding between the spike glycoprotein receptor binding domain (RBD) of the virus and the cellular receptor angiotensin-converting enzyme 2 (ACE2). A competition assay indicated different epitopes on the RBD for these two antibodies, making them a potentially promising virus-targeting monoclonal antibody pair for avoiding immune escape in future clinical applications. Moreover, a therapeutic study in a mouse model validated that these antibodies can reduce virus titers in infected lungs. The RBD-B38 complex structure revealed that most residues on the epitope overlap with the RBD-ACE2 binding interface, explaining the blocking effect and neutralizing capacity. Our results highlight the promise of antibody-based therapeutics and provide a structural basis for rational vaccine design.